Flexible Diamond Fibers for High‐Energy‐Density Zinc‐Ion Supercapacitors. Issue 44 (2nd September 2020) - Jian, Ze; Yang, Nianjun; Vogel, Michael; Leith, Stewart; Schulte, Anna; Schönherr, Holger; Jiao, Tianpeng; Zhang, Wenjun; Müller, Julian; Butz, Benjamin; Jiang, Xin
Abstract: Supercapacitors supply high power densities but suffer from low energy densities and small specific capacitances. The design and implementation of unique capacitor electrodes are expected to overcome these challenges. Herein, flexible diamond fibers (a fibrous core/shell structure of diamond/carbon fibers) are produced through overgrowing conductive carbon fibers core with a thin boron‐doped diamond film as a shell using a chemical vapor deposition technique. The resultant fibers combine the properties of boron‐doped diamond with those of carbon fibers. This allows these binder‐free diamond fibers to be employed as the positive electrode in the fabrication of zinc‐ion supercapacitors. Together with a negative electrode fabricated from zinc nanosheet coated diamond fibers, this diamond supercapacitor delivers a high and stable specific capacitance. More importantly, it delivers high gravimetric and volumetric energy and power densities, even under severe bending states. The performance of this flexible supercapacitor is superior to previous diamond and carbon fiber‐based supercapacitors. Such flexible diamond supercapacitors are promising energy storage devices for various flexible electronics. Abstract : Diamond fibers, fibrous core/shell structure of diamond/carbon fibers, featuring high‐capacitor performance and flexibility are developed by depositing boron‐doped diamond shell onto a carbon fibers core. Zinc‐ion supercapacitors constructed using these diamond fibers possess high gravimetric and volumetric energy and power densities, along with long‐term stability and high flexibility. Its performance is superior than most of the previously reported diamond and carbon fiber‐based supercapacitors.